Fragmentation of an aflatoxin‐like gene cluster in a forest pathogen. Issue 2 (1st March 2013) - Bradshaw, Rosie E.; Slot, Jason C.; Moore, Geromy G.; Chettri, Pranav; de Wit, Pierre J. G. M.; Ehrlich, Kenneth C.; Ganley, Austen R. D.; Olson, Malin A.; Rokas, Antonis; Carbone, Ignazio; Cox, Murray P.
Summary: Plant pathogens use a complex arsenal of weapons, such as toxic secondary metabolites, to invade and destroy their hosts. Knowledge of how secondary metabolite pathways evolved is central to understanding the evolution of host specificity. The secondary metabolite dothistromin is structurally similar to aflatoxins and is produced by the fungal pine pathogen Dothistroma septosporum . Our study focused on dothistromin genes, which are widely dispersed across one chromosome, to determine whether this unusual distributed arrangement evolved from an ancestral cluster. We combined comparative genomics and population genetics approaches to elucidate the origins of the dispersed arrangement of dothistromin genes over a broad evolutionary time‐scale at the phylum, class and species levels. Orthologs of dothistromin genes were found in two major classes of fungi. Their organization is consistent with clustering of core pathway genes in a common ancestor, but with intermediate cluster fragmentation states in the Dothideomycetes fungi. Recombination hotspots in a D. septosporum population matched sites of gene acquisition and cluster fragmentation at higher evolutionary levels. The results suggest that fragmentation of a larger ancestral cluster gave rise to the arrangement seen in D. septosporum . We propose that cluster fragmentation may facilitate metabolic retooling and subsequent host adaptation of plant pathogens.